Regulation of implantation and establishment of pregnancy in mammals : tribute to 45 year anniversary of Roger V. Short's "Maternal recognition of pregnancy" /: tribute to 45 year anniversary of Roger V. Short's "Maternal recognition of pregnancy". ([2015]) - Unknown
No abstract available